Application of Augmented Reality and Virtual Reality Google Expeditions in Social Studies Learning in Junior High School - Sania Malya M; Satia Puspawati; Putri Halimatussya'diah (Generasi Sains Indonesia, 2025)
This study examines the application of Augmented Reality (AR) and Virtual Reality (VR) technologies, to find out the implementation of digital media in social studies learning through google expeditions in junior high school. AR and VR provide immersive and interactive learning experiences that significantly enhance students' understanding of abstract concepts and historical events. Although previous studies have demonstrated high student engagement and improved conceptual understanding through these technologies, a striking digital divide remains, particularly between urban and rural areas. Using a qualitative case study approach, this study emphasizes the empirical impact and personal experiences of integrating AR/VR in education. Findings suggest that AR and VR can enhance students' interest, retention, and comprehension, making them valuable tools in modern pedagogy.